Data assimilation and parameter estimation via ensemble Kalman filter coupled with stochastic moment equations of transient groundwater flow. Issue 3 (6th March 2013) - Panzeri, M.; Riva, M.; Guadagnini, A.; Neuman, S. P.
Key Points Embedding stochastic moment equations of flow in ensemble Kalman filter Avoiding need for Monte Carlo simulations in ensemble Kalman filter Avoiding need for batch inversion of Moment Equations